Rekonstruksi Pembuktian Mens Rea bagi Kurir Narkoba Berdasarkan Doktrin Willful Blindness - Linda Ikawati; Rengga Kusuma Putra; Satriya Nugraha; Retno Eko Mardani; Aziz Widhi Nugroho (PMIH Untag Semarang, 2026)
Narcotics law enforcement in Indonesia faces a paradoxical crisis where repressive criminal policies coexist with simplified evidence standards that often overlook the fundamental element of criminal liability: mens rea. Legal practice frequently adopts a de facto strict liability approach, where physical possession of narcotics automatically equates to guilty intent. This creates a substantive injustice, particularly for